The Application For A Polygamy Permit Is Reviewed From An Islamic Legal Perspective (Analysis of PA.Depok Decision No. 3051/Pdt.G/2020/PA.Dpk) - Ameliah, Elvita; Songgirin, Amin (Indonesian Scientific Publication, 2023)
Polygamy or having more than one wife is permissible under the provisions of Islamic law and positive law. Even though the large number of polygamy in our society has never been investigated in research what the real motives and causes are, in reality most polygamy is carried out by our society not in accordance with all the provisions, so that the polygamy that is carried out is very far from the wisdom and secrets contained therein. The permissibility of practicing polygamy according to Islam in many cases is often implemented and implemented. This causes many things to happen at will, without paying attention to and heeding the conditions that must be met. The problems in this thesis are how the judge considers in the decision on the case for a polygamy permit application No.3051/Pdt. G/2020/PA.D pk and what are the aspects of justice for polygamy applicants. This research method uses normative juridical research or a normative legal approach and is commonly called library research. The data collection technique in this research is library research which originates from laws and regulations, books, publications and research results. Based on the research results it is known that: 1). In determining the decision on the principle of proving the polygamy licensing case, the judge considered that the respondent did not mind polygamy by her husband, referring to Law No. 1 of 1974 to serve as a guideline in resolving polygamy problems. However, the judge did not grant the petitioner's request. 2). The concept of fairness in polygamy, according to the judge, goes back to Islamic teachings, namely justice that is meant is justice that is material in nature that can be controlled by the husband and becomes his ability, such as good treatment, sharing of time in spending the night, and giving a living. As for those related to the heart, then she may not be able to do it, because it is beyond the husband's control or beyond his ability, such as feelings of love and inclinations of the heart. So in this case the husband is not required to make it happen because it is beyond human power which is impossible to fulfill. Then the judge saw the fairness of the decision by looking at the statement made by the husband to be able to act fairly in guaranteeing the needs of his wives and children.